The influence of adversity quotient on nurses’ job performance during the COVID-19 Pandemic at Batam City Health Centers - Syarif, Arman (Goodwood Publishing, 2024)
Purpose: This study explores the effect of Adversity Quotient (AQ) on nurse job performance, with motivation as a mediating factor, especially during the COVID-19 crisis. Methodology: Employing a quantitative, explanatory research design, the study collected data from 137 nurses at community health centers (Puskesmas) in Batam, Indonesia. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine both direct and indirect effects. Results: AQ significantly boosts motivation but does not directly affect performance. Motivation has a strong positive impact on performance and fully mediates the AQ–performance link, showing that resilience must be channeled through motivation to influence behavior. Conclusions: The research concludes that AQ alone is insufficient to enhance performance it requires the presence of motivation to translate resilience into tangible outcomes. This highlights the importance of fostering motivational support in healthcare environments Limitations: The study’s generalizability is limited to nurses in Batam and is constrained by its cross-sectional design and self-reported data, which may introduce bias. Contribution: This study strengthens the integration of adversity quotient theory with self-determination theory by validating the mediating role of intrinsic motivation. It contributes a psychological model where motivation serves as a catalyst for transforming resilience into effective job behavior.